Composition for packaging film

By using a film lining made of a polymer resin composition containing ionomers and specific additives, the problem of degradation of characteristics of existing food packaging films after thinning is solved, and high wear resistance in the presence of oils and seasonings is achieved It is scratch-resistant, and maintains the shelf life of food products, while also being recyclable.

CN119497735APending Publication Date: 2025-02-21DOW GLOBAL TECHNOLOGIES LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380050728.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-26
Filing Date
2023-07-25
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing food packaging films cannot maintain wear-resistant, scratch-resistant and shelf-life characteristics after thinning, especially in the presence of oils and seasonings.

Method used

A polymer resin composition comprising ionomers and specific additives is used for the production of wear and scratch resistant film linings. The composition includes 20% to 100% ionomer resin, 0.5% to 5% anti-slip additive, 0.25% to 3% anti-blocking additive, and 0.1% to 3% cooling roller release additive.

Benefits of technology

The film lining maintains a high level of wear and scratch resistance in the presence of oil and seasonings and can be thinned to 80% without affecting the shelf life of food products, while also recyclable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215451280000201
    Figure BDA0005215451280000201
  • Figure BDA0005215451280000211
    Figure BDA0005215451280000211
  • Figure BDA0005215451280000261
    Figure BDA0005215451280000261
Patent Text Reader

Abstract

A composition for making a wear resistant film, the composition comprising: (a) at least one ionomer of an acid copolymer; (b) at least one anti-slip additive; (c) at least one anti-adhesion additive; (d) at least one chilled roll release additive; and (e) optionally, one or more additives different from components (a)-(d); a method for producing the above film composition; a single-layer wear-resistant film or a multi-layer wear-resistant film, wherein at least one layer of the single-layer film or the multi-layer film comprises a wear-resistant film layer made of the film composition described above; and a method for manufacturing the single-layer film or the multi-layer film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition for making a packaging film; and more particularly, the present invention relates to a composition for making a wear-resistant and scratch-resistant film for a packaging container used in food packaging. Background Art

[0002] It is believed that using recycled materials is better for the environment and reduces the waste of natural resources for disposable products. Therefore, many industries wish to use recyclable materials in products and / or product packaging to provide the recovery of disposable products and the reduction of natural resources. In the packaging industry, the current structure of some containers for various food contact packaging applications is usually made of a combination of various materials, some of which are recyclable, and some materials are non-recyclable. Producing final food packaging containers with non-recyclable materials makes it difficult and impossible to recycle this food packaging container in some cases once this container is discarded. For example, a packaging container (for example, bottle, bag, pouch, such as pouch bags such as pillow bags or cans such as composite cans) for packaging food products may include a multilayer structure, which includes several layers of different materials, such as a combination of paper, gas and / or moisture barrier materials and polymer resin layers.

[0003] Typically, in the construction of containers for food packaging having a multi-layer film structure, the innermost film layer of the container (i.e., the "film liner") is in contact with the food product and needs to meet many key quality requirements, such as: (1) high abrasion and scratch resistance; (2) extending the shelf life of the packaged food product; and (3) excellent sealing performance.

[0004] To date, film liners used in food contact applications have been successfully made from ionomer polymer resins based on copolymers of ethylene and methacrylic acid, such as SURLYN® available from The Dow Chemical Company. TM Such film liners generally have some good properties, such as high abrasion resistance, scratch resistance, long shelf life, improved sealing performance; and recyclability; and such film liners have achieved some success in providing packaging multilayer films for food packaging. However, in some cases, the packaging industry desires to thin the film liner of a multilayer packaging container to save the amount of material used in the manufacture of the packaging container while maintaining the above-mentioned good properties. Unfortunately, it has been found that when the inner layer (film liner) made of a previously known ionomer composition is thinned, the shelf life of the food product in contact with the thinned film liner is significantly reduced.

[0005] It would be desirable to provide an alternative ionomer composition that can be used to make abrasion and scratch resistant films, such as film liners for packaging applications, wherein the film liners, in addition to being recyclable, can be thinned without compromising the abrasion, scratch, oil and seasoning resistance properties of the thinned film liners and / or without compromising the shelf life of the packaged food product. Summary of the invention

[0006] One general embodiment of the present invention relates to a polymer resin composition or formulation for producing abrasion-resistant and scratch-resistant films (abbreviated herein as "ARF") for packaging applications. The polymer resin composition of the present invention comprises a combination of an ionomer and several additives, wherein the additives are used at unique levels so that the ARF manufactured from the resin composition containing such additives advantageously has a high level of abrasion resistance and scratch resistance in the presence of oils and seasonings. In addition, the manufactured container packaging product includes an ARF layer of the present invention, such as a film liner for a container, wherein in a general embodiment, the film liner can be advantageously thinned from 0% (no thinning) to 80% without adversely affecting the shelf life of food products in contact with the ARF. In addition, the manufactured container packaging product of the present invention can be recyclable.

[0007] In a preferred embodiment of the present invention, the film composition comprises, for example, the following components:

[0008] (a) 20 to 100 weight percent of at least one ionomer resin comprising ethylene copolymerized with an acid such as (meth)acrylic acid groups; wherein the at least one ionomer resin contains selective ions of sodium, zinc, iron, magnesium; has improved abrasion resistance, scratch resistance, chemical resistance; and resistance to oils, salts and seasonings; and

[0009] and in a general embodiment, having a selective neutralized acid level of >5%, a selective free acid level of >7%, and a selective total acid level of >13%;

[0010] (b) 0.5 wt % to 5 wt % of at least one anti-slip additive in the form of a masterbatch material made from ethylene (meth)acrylic acid copolymer; wherein the at least one anti-slip additive has one or more of the following properties: a slow blooming long chain fatty acid amide or aliphatic amide;

[0011] (c) 0.25 wt % to 3 wt % of at least one anti-blocking additive in the form of a masterbatch material made from ethylene (meth) acrylic acid copolymer as a carrier resin; wherein the at least one anti-blocking additive has one or more of the following characteristics: is a non-migrating substance, including, for example, a non-migrating organic compound or an inorganic synthetic mineral or natural mineral particle;

[0012] (d) 0.1 wt % to 3 wt % of at least one chill roll release additive in the form of a masterbatch material made from an ethylene (meth)acrylic acid copolymer as a carrier resin; wherein the at least one chill roll release additive has one or more of the following properties: fast blooming long chain fatty acid amides and primary amides; and

[0013] (e) optionally, one or more further additives different from components (b) to (d).

[0014] In another embodiment, the present invention is directed to a monolayer or multilayer film made from the above film composition.

[0015] In yet another embodiment, the present invention is directed to a manufactured container packaging product having a multi-layer packaging structure comprising at least one inner ARF layer made from the above-described film composition.

[0016] In other embodiments, the present invention relates to methods for preparing the above-mentioned formulations, preparing the above-mentioned ARF layers, and preparing the above-mentioned multilayer packaging structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a cross-sectional view of a tank container of the present invention showing the different layers of the container wall.

[0018] Figure 2 is a black and white image of a perspective elevation view of a prior art membrane sheet showing a region of the membrane sheet before it is subjected to a wear process.

[0019] Figure 3 is a black and white image of a perspective elevation view of a prior art membrane sheet showing the worn and scratched areas of the membrane sheet after the membrane sheet has been subjected to a wear process.

[0020] Figure 4 is a black and white image of a perspective elevation view of a membrane sheet of the present invention showing a region of the membrane sheet before it is subjected to a wear process.

[0021] Figure 5 is a black and white image of a perspective elevation view of a membrane sheet of the present invention showing the worn and scratched areas of the membrane sheet after the membrane sheet has been subjected to a wear process.

[0022] Figure 6 is a black and white image of a perspective elevation view of another prior art membrane sheet showing the worn and scratched areas of the membrane sheet after the membrane sheet has been subjected to a wear process.

[0023] Figure 7 is a black and white image of a perspective elevation view of another film sheet of the present invention showing the worn and scratched areas of the film sheet after the film sheet has been subjected to a wear process. Figure 7 The membrane sheet can be Figure 6 The membrane sheets were compared. DETAILED DESCRIPTION

[0024] Reference will now be made in detail to embodiments of ARFs made from film compositions comprising an ionomer polymer resin based on a copolymer of ethylene and (meth)acrylic acid. The ARFs may be used in food product packaging applications; however, it should be noted that this is merely an exemplary illustrative implementation of the embodiments disclosed herein. These embodiments may be applied to other packaging technologies that require incorporation of a film material that (1) has high abrasion and scratch resistance properties, (2) may be thinned while maintaining its properties, (3) is recyclable, and (4) is resistant to oils, greases, and seasonings when present in and around the packaged food product.

[0025] The term "composition" refers to a mixture of materials comprising the composition, as well as reaction products and decomposition products formed from the materials of the composition.

[0026] The term "recyclability" herein with respect to packaging articles that include paper as a recyclable material refers to the property of a packaging article whereby the article is capable of being processed through a paper recovery and repulping process to recover the paper of the packaging article and convert the recovered paper back into pulp. For example, in one embodiment, the paper recovery and repulping process includes the steps of: (1) shredding the packaging article containing paper; (2) immersing the shredded article in an aqueous solution that breaks up and separates the fibers into pulp; (3) filtering to separate the pulp from any debris including plastic film; and (4) recovering the separated pulp and (5) converting the recovered pulp back into a recycled paper product. As known to those skilled in the art, in one embodiment, one method of determining the recyclability of paper is by determining the pulp yield, i.e., how much reusable pulp is collected during the repulping process.

[0027] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing monomers of the same or different types. The general term "polymer" thus encompasses: (1) the term homopolymer (used to refer to polymers prepared by polymerizing only one type of monomer, it being understood that trace amounts of impurities may be incorporated into the polymer structure); and (2) the term copolymer or interpolymer (used to refer to polymers prepared by polymerizing two or more different monomers, it being understood that trace amounts of impurities may be incorporated into the polymer structure). Trace amounts of impurities (e.g., catalyst residues) may be incorporated into and / or within the polymer. The polymer may be a single polymer or a polymer blend.

[0028] "Interpolymer" refers to a polymer prepared by polymerizing at least two different types of monomers. Thus, the generic term interpolymer includes copolymers and other polymers prepared by polymerizing two or more different monomers (such as terpolymers).

[0029] "Ionomers" are copolymers of ethylene and ethylenically unsaturated monocarboxylic acids whose carboxylic acid groups are partially neutralized by metal ions such as sodium or zinc. Useful ionomers herein include those in which there are sufficient metal ions in the ionomer to neutralize 15% to 60% (neutralization percentage) of the acid groups in the ionomer. Carboxylic acids include, for example, "(meth)acrylic acid". "(Meth)acrylic acid" herein refers to acrylic acid and / or methacrylic acid. Useful ionomers (or "partially neutralized ethylene acid copolymers") include those having at least 50% by weight of ethylene units in one embodiment, 50% to 90% by weight of ethylene units in another embodiment, and 80% to 90% by weight of ethylene units in yet another embodiment. Useful ionomers also include those having 1% to 20% by weight of acid units.

[0030] As used herein, the terms "comprising," "including," "having," and derivatives thereof are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequently recited any other components, steps, or procedures, except those that are not essential to operability. The term "consisting of excludes any ingredient, step, or procedure not specifically recited or listed.

[0031] As used throughout this specification, the abbreviations given below have the following meanings, unless the context clearly indicates otherwise: "=" means "equal to"; "<" means "less than"; ">" means "greater than"; "≤" means "less than or equal to"; "≥" means "greater than or equal to"; "I2" means "melt index at 190 degrees Celsius with 2.16 kilograms of weight applied"; g = gram; mg = milligram; pts = parts by weight; kg = kilogram; kg / h = kilogram per hour; g / cc = gram per cubic centimeter; kg / m 3 = kilogram per cubic meter; g / mol = gram per mole; L = liter; mL = milliliter; g / L = gram per liter; Mw = mass molecular weight; Mn = number molecular weight; Mz = z-average molecular weight; m = meter; μm = micrometer; mm = millimeter; cm = centimeter; min = minute; s = second; mm / s 2= millimeter per square second; mm / s = millimeter per second; ms = millisecond; hr = hour; mm / min = millimeter per minute; m / s = meter per second; ℃ = degrees Celsius; C / min = degrees Celsius per minute; mPa.s = millipascal-second; MPa = megapascal; kPa = kilopascal; Pa.s / m 2 = Pascal-second per square meter; N = Newton; cN = hundredth of a Newton; rpm = revolutions per minute; mm 2 = square millimeters; g / 10min = grams per 10 minutes; J = joule; J / g = joule per gram; % = percent; eq% = equivalent percent; vol% = volume percent; and wt% = weight percent.

[0032] Unless otherwise indicated, all percentages, parts, ratios and similar amounts are defined by weight. For example, unless otherwise indicated, all percentages described herein are weight percentages (wt%).

[0033] Unless otherwise specified, temperatures are expressed in degrees Celsius (°C), and "ambient temperature" means between 20°C and 25°C.

[0034] In a broad embodiment, the present invention is directed to a resin formulation or composition useful for preparing food product packaging films, comprising, for example, a combination, blend or mixture of: (a) at least one ionomer of an acid copolymer; (b) at least one anti-slip additive (e.g., CONPOL TM 20S1); (c) at least one anti-blocking additive (e.g., CONPOL TM 13B); (d) at least one anti-blocking additive (e.g., CONPOL TM 5R); and (e) optionally, if desired, one or more additives different from components (b) to (d).

[0035] In some embodiments, the above-mentioned resin combination is advantageously used to manufacture film products, such as monolayer films or multilayer films. In one embodiment, the film product is incorporated into a multilayer structure (that is, a structure including various different substrate layers) food product packaging container, wherein the film product of the present invention is at least one substrate layer of a multilayer structure. The film product of the present invention can be a monolayer film or a multilayer film, wherein at least one layer of at least one monolayer film or multilayer film includes at least one substrate layer of the multilayer structure constituting the food product packaging container. In one embodiment, the film product of the present invention of a substrate in the substrate constituting the food product packaging container is a film lining directly contacted with the food product packaged in the food product packaging container.

[0036] Before the film product is manufactured by the above-mentioned resin combination, the resin combination is first processed into pellets. For example, the components (a)-(d) and optional (e) of the blend formulation are melt blended (by melt mixing, for example, via an extruder) to manufacture a melt blend formulation. Then, the melt blend formulation is sent from an extruder (such as a twin screw extruder) into a pelletizer by a wire die to form a pellet of the blend formulation. Once made, the pellets are then processed to manufacture a film product showing desired wear-resistant and scratch-resistant properties.

[0037] In some embodiments, the film resin composition comprises, for example:

[0038] (a) 20 to 100 weight percent of at least one ionomer resin comprising ethylene copolymerized with acid groups, such as (meth)acrylic acid groups; and wherein the at least one ionomer resin has several advantages, including a beneficial acid content percentage, a selective ion type, and a lower limit on ion concentration;

[0039] (b) at least one anti-slip additive provided as a masterbatch material made of ethylene (meth) acrylic acid copolymer and an anti-slip additive; wherein the anti-slip additive content in the masterbatch is 5 wt % to 25 wt % based on the total concentration of one or more different anti-slip additives used in the masterbatch, for example, in one embodiment, the anti-slip additive may be CONPOL TM 5B10S1 and CONPOL TM S1 combination, and the anti-slip additive concentration can be 10% CONPOL TM 5B10S1 and 20% CONPOL TM S1; and wherein at least one anti-slip additive has the following characteristics: a slow blooming long-chain fatty acid amide or aliphatic amide;

[0040] (c) at least one anti-blocking additive provided as a masterbatch material made of ethylene (meth) acrylic acid copolymer and an anti-blocking additive; wherein the anti-blocking additive content in the masterbatch is 3 wt % to 25 wt % based on the total concentration of one or more different anti-blocking additives used in the masterbatch, for example, in one embodiment, the anti-blocking additive can be CONPOL TM 5B10S1 and CONPOL TM 20B combination, and the concentration of the anti-blocking additive may be 5% CONPOL TM 5B10S1 and 20% CONPOL TM 20B; and wherein at least one anti-blocking additive has the characteristics of being, for example, a non-migrating substance, including, for example, a non-migrating organic or inorganic compound, a synthetic mineral or a natural mineral particle;

[0041] (d) at least one chill roll release additive provided as a masterbatch material made of ethylene (meth) acrylic acid copolymer and a chill roll release additive; wherein the chill roll release additive content in the masterbatch is from 3 wt % to 10 wt % based on the total concentration of one or more of the various chill roll release additives used in the masterbatch, for example, in one embodiment, the chill roll release additive may be CONPOL TM 5R, and the concentration of the cooling roll release additive can be 5% CONPOL TM 5R; and wherein at least one chill roll release additive has the characteristics of a fast blooming long chain fatty acid amide and a primary amide; and

[0042] (e) Optionally, one or more further additives different from additive components (b) to (d).

[0043] In a general embodiment of the present invention, the film resin composition that can be used to prepare the film includes, for example, at least one ionomer resin. Examples of ionomer resins, i.e., component (a), that can be used to prepare the film composition of the present invention include, for example, one or more polyolefins having one or more acidic functional groups, wherein the acidic functional groups are neutralized by metal ions. The one or more acidic functional groups may include, for example, carboxylic acids, maleic anhydride, fumaric acid, etc.; and mixtures thereof. The metal ions may include, for example, sodium, zinc, iron, magnesium, etc.; and mixtures thereof. An example of a preferred embodiment of the ionomer resin includes ethylene copolymerized with acid groups such as (meth) acrylic acid groups.

[0044] Examples of some commercially available ionomer resins that can be used to prepare the membrane compositions of the present invention include, for example: SURLYN TM Resin (available from The Dow Chemical Company); Primacor TM IO (available from SK Global Chemical Co. Ltd.); and mixtures thereof.

[0045] The ionomer resin used to prepare the film composition, i.e., component (a), may be present in the composition generally in an amount of 20 wt % to 100 wt % in one embodiment, 30 wt % to 100 wt % in another embodiment, and 50 wt % to 100 wt % in yet another embodiment, based on the total amount of components in the film composition. Below the general range of ionomer resins described above, the abrasion and scratch resistance properties of the packaging film in the presence of oils / flavors are insufficient to provide the protection required for packaging applications.

[0046] In one general embodiment of the present invention, a film composition useful for preparing a film liner comprises, for example, at least one anti-slip additive, component (b), in the form of a masterbatch material made with an ethylene (meth)acrylic acid copolymer as a carrier resin.

[0047] The anti-slip additive, component (b), can be obtained in pellet form, and a plurality of pellets are blended with the ionomer resin, component (a), to modify the surface properties of the resulting film product made from the film resin composition. For example, the anti-slip additive blooms to the film surface over time and can be used to modify the coefficient of friction (COF) of the surface of the film made from the film composition. In some embodiments, the anti-slip additive can also reduce online blocking during film extrusion and offline film blocking during film roll unwinding.

[0048] Examples of anti-slip additives, i.e., component (b), that can be used to prepare the film composition of the present invention include, for example, slow blooming long chain fatty acid amides, aliphatic amides, and mixtures thereof. In a preferred embodiment, the anti-slip additives include, for example, oleyl palmitamide, erucamide, and mixtures thereof.

[0049] Examples of some commercially available anti-slip additives, component (b), that can be used to prepare the film composition of the present invention include, for example: CONPOL TM (available from The Dow Chemical Company); Ampacet 10090 (available from Ampacet Corp); Crodamide ER TM (available from CRODA); and mixtures thereof.

[0050] The anti-slip additive used to prepare the film composition, i.e., component (b), can be present in the composition typically in the following amounts, based on the total amount of components in the film composition: >0.05 wt % in one embodiment; >0.05 wt % to 6 wt % in another embodiment; 0.1 wt % to 5 wt % in yet another embodiment; 0.1 wt % to 3 wt % in yet another embodiment; and 0.88 wt % to 1.5 wt % in yet another embodiment.

[0051] Below the above typical ranges for anti-slip additives, the COF of the film becomes too high, and as a result, the high COF reduces packaging production yields. In addition, below the above typical ranges for anti-slip additives, the wear and scratch resistance of the packaging film in the presence of oils / seasonings may be reduced and adversely affect the protection required for packaging applications. Above the above typical ranges for anti-slip additives, the anti-slip additive may precipitate, film winding problems may occur, and the sealing properties of the film may be reduced.

[0052] In one general embodiment of the present invention, the film composition useful for preparing the film liner comprises, for example, at least one antiblocking additive, component (c), in the form of a masterbatch material made with ethylene (meth)acrylic acid copolymer as a carrier resin.

[0053] Anti-blocking additive, i.e. component (c), can be obtained in the form of pellets, and multiple pellets are blended with ionomer resin, i.e. component (a), to change the surface characteristics of the resulting film product made of the film composition. For example, anti-blocking additives can be used to modify the surface of the film made of the film composition to prevent bubble adhesion, such as when the film is manufactured as an inner layer on a blown film production line. Anti-blocking additives also help to reduce the energy required to unwind the film roll. And, anti-blocking additives help to reduce the COF of the film. All of the above-mentioned beneficial results using anti-blocking additives help to improve the production yield of the film.

[0054] Examples of anti-blocking additives, i.e., component (c), that can be used to prepare the film composition of the present invention include, for example, diatomaceous earth (silicon dioxide), talc (magnesium silicate), synthetic silica (silicon dioxide), calcium carbonate, aluminosilicate ceramics, clay (aluminum silicate), mica (potassium aluminum silicate), stearyl erucamide, zinc stearate, silicone, glyceryl monostearate, ethylene bisstearamide, and mixtures thereof. In a preferred embodiment, the anti-blocking additive includes, for example, silicon dioxide, talc, and mixtures thereof.

[0055] Examples of some commercially available antiblocking additives, component (c), that can be used to prepare the film compositions of the present invention include, for example: CONPOL TM 13B, CONPOL TM 20B, CONPOL TM 5B10S1 and CONPOL TM 20T (both available from The Dow Chemical Company); and Crodamide BR (available from CRODA); and Ampacet 10063 (available from Ampacet Corp); and mixtures thereof.

[0056] The anti-blocking additive used to prepare the film composition, i.e., component (c), may be present in the composition typically in an amount of: >0.05 wt % in one embodiment; >0.05 wt % to 6 wt % in another embodiment; >0.1 wt % to 5 wt % in yet another embodiment; >0.1 wt % to 3 wt % in yet another embodiment; and >0.5 wt % to 1 wt % in yet another embodiment, based on the total amount of components in the film composition.

[0057] Below the typical range for anti-blocking additives, the line operator will have difficulty unrolling the resulting film. Above the typical range for anti-blocking additives, the haze characteristics of the film will increase and the sealing properties of the film will decrease.

[0058] In one general embodiment of the invention, film compositions useful for preparing film liners include, for example, at least one chill roll release additive, component (d), in the form of a masterbatch material made with ethylene (meth)acrylic acid copolymer as a carrier resin.

[0059] The chill roll release additive, component (d), can be obtained in pellet form, and a plurality of pellets are blended with the ionomer resin, component (a), to modify the surface properties of the resulting film article made from the film composition. For example, the chill roll release additive tends to migrate to the film surface between the film and the chill roll; thus, the chill roll release additive can be used to modify the surface of the film made from the film composition to prevent the film from adhering to the chill roll.

[0060] Examples of chill roll release additives, i.e., component (d), that can be used to prepare the film compositions of the present invention include long chain fatty acid amides and primary amides, for example, that bloom quickly. In some embodiments, for example, the amides can be saturated or unsaturated; and can include from oleyl (18 carbon atoms) to erucic acid (22 carbon atoms); and mixtures thereof. In preferred embodiments, the chill roll release additives include, for example, oleamide, behenamide, and mixtures thereof.

[0061] Examples of some commercially available chill roll release additives, component (d), that can be used to prepare the film compositions of the present invention include, for example: CONPOL TM (available from The Dow Chemical Company); Ampacet TM (available from Ampacet Corp); Crodamide (available from CRODA); and mixtures thereof.

[0062] The chill roll release additive used to prepare the film composition, i.e., component (d), can be present in the composition typically in an amount of >0.05 wt % in one embodiment; 0.05 wt % to 6 wt % in another embodiment; 0.05 wt % to 5 wt % in yet another embodiment; 0.1 wt % to 2 wt % in yet another embodiment; and 0.15 wt % to 1 wt % in yet another embodiment, based on the total amount of components in the film composition.

[0063] Below the typical range for chill roll release additives above, the resulting film will stick to the chill roll to the extent that the film may break and the line operator will need to stop and restart the line. Above the typical range for chill roll release additives above, any further improvement will be minimal.

[0064] In another embodiment, the film composition of the present invention may include a variety of other optional additives. The additives combined with the composition of the present invention can be formulated to achieve the performance of a specific function while maintaining the excellent benefits / characteristics of the composition. For example, the following additives can be blended into the formulated resin composition to form the film composition of the present invention, and these additives include: antioxidants; antifogging agents; pigments; colorants; ultraviolet stabilizers; UV absorbers; processing aids; fillers; compatibilizers; other ionomer resins different from component (a); other anti-slip additives (migratory and non-migratory anti-slip additives) different from component (b); other anti-blocking additives different from component (c); other cooling roll demoulding additives different from component (d); etc.; and mixtures thereof.

[0065] When used in the film composition, the optional additives may be present in the film composition in an amount of <10 wt % in one general embodiment, <5 wt % in another embodiment, <3 wt % in yet another embodiment, and <1 wt % in yet another embodiment. In other embodiments, the optional additives may be added to the film composition in an amount generally ranging from 0 wt % to <10 wt % in one embodiment; 0.1 wt % to <10 wt % in another embodiment, 0.1 wt % to <5 wt % in yet another embodiment; 0.1 wt % to <3 wt % in yet another embodiment, and 0.1 wt % to <1 wt % in yet another embodiment, based on the total amount of components in the film composition.

[0066] In a broad embodiment of the present invention, the method for making a film resin composition includes, for example, mixing or blending the above-mentioned components (a), (b), (c) and (d); and any desired optional component (e) as described above. Both dry blending processes and melt blending processes (compounding processes) known to those skilled in the art of mixed polymer resins can be used. For example, in a general embodiment, the dry blending process includes mixing all polymer pellets together using a drum or ribbon mixer or any equivalent dry mixer. For example, in a general embodiment, the compounding (or melt blending) process includes melt mixing components (a), (b), (c), (d) and optional (e) at a temperature of 80°C to 285°C in a mixing device known to those skilled in the art, such as a twin-screw extruder, a single-screw extruder, a continuous mixer or an intermittent mixer to form a homogeneous melt;

[0067] Some advantageous / beneficial properties exhibited by the film composition produced according to the above-mentioned mixing or compounding process may include, for example: the film composition can be easily produced, that is, the different components (a), (b), (c), (d) and optionally (e) of the composition can be easily and more evenly (consistently or homogeneously) dispersed; and the processability of the composition is improved, that is, food product packaging film can be easily manufactured by easily processing the composition.

[0068] As disclosed below, when the above-described compositions are used to make ARFs, the films exhibit exceptionally improved properties, such as one or more of the following: improved abrasion and scratch resistance in the presence of vegetable oils, salt, vinegar, spices, and other seasonings, while maintaining chemical resistance, sealant gap filling, low heat seal initiation temperature, and high hot tack strength to meet other requirements of the target applications.

[0069] It is assumed (but not limited to this) that the reason for the improved abrasion / scratch resistance in the presence of vegetable oils, fats or greasy substances included in foods and sauces is because the total acid content and the neutralization percentage of the composition of the present invention are proportionally increased compared to known films. It has been shown that the increased total acid content and the neutralization percentage lead to increased chemical or food product resistance, toughness and hardness.

[0070] In some embodiments, the present invention relates to the production of ARF from the above-mentioned film composition and pellets. ARF can be used as an inner layer (or film lining) for incorporation into packaging containers used in food product packaging applications, wherein the ARF layer is in contact with the food product. The ARF layer of the present invention has a combination of good properties, such as high levels of abrasion resistance and scratch resistance in the presence of oils and seasonings; in a general embodiment, the ARF layer of the present invention can be thinned by up to 80% without adversely affecting the shelf life of the food product in contact with the ARF layer; and the container packaging product having the ARF layer of the present invention can be recyclable.

[0071] In some embodiments, the above film composition can be manufactured into an ARF component having a wear resistance grade value Y of >6.0 according to the following equation (I):

[0072]

[0073] wherein Y is an abrasion resistance rating of >6.0; wherein A is the average tensile stress at break in the transverse direction of the film member; wherein B is the average tensile stress at break in the longitudinal direction of the film member; and wherein C is the average normalized Elmendorf tear in the transverse direction of the film member.

[0074] Equation (I) can be used to help predict the wear resistance of wear films, based on the key physical properties A, B, and C that can be measured by standard ASTM methods, quantified by Y. To determine equation (I), a multiple linear regression was performed using software in which the input of the continuous response variable Y was determined for each of the comparative examples and the embodiments of the present invention by the experimental wear resistance rating method. The software used is commercial software, including JMP, a computer program for statistical analysis developed by JMP, a subsidiary of SAS Institute. The wear resistance rating method is described in detail in the test methods section, and for each embodiment, the measured values ​​of Y are shown in Table V. The inputs for the categorical response variables A, B, and C are the measured physical properties of the comparative examples and the embodiments of the present invention, which are also included in Table V. The coefficient of determination value R of equation (I) based on multiple linear regression 2 (Its range can be from 0 to 1) For example, it is 0.975.

[0075] In some embodiments, the wear resistance grade value Y of the ARF component can be, for example, ≥6 to 9 in one general embodiment, ≥6 to 8 in another embodiment, and ≥6 to 7 in yet another embodiment.

[0076] In a broad embodiment of the present invention, the above-described membrane composition is used to make an ARF, such as a membrane liner. The membrane composition as described above can be, for example, a resin formulation or composition comprising a combination, blend or mixture of: (a) at least one ionomer of an acid copolymer; (b) at least one anti-slip additive, such as CONPOL TM 20S1; (c) at least one anti-blocking additive such as CONPOL TM 13B; (d) at least one chill roll release additive such as CONPOL TM 5R; and (e) optionally, if desired, one or more additives different from components (a) to (d).

[0077] Single layer ARF structures include, for example, a sheet of film of any desired length and width; and having, for example, a thickness of 5 μm to 380 μm in one general embodiment; 10 μm to 250 μm in another embodiment; and 10 μm to 100 μm in yet another embodiment.

[0078] In a broad embodiment of the present invention, a method for making a monolayer film includes, for example, using any conventional film forming method, such as cast film method, blown film method, extrusion coating method and other methods and equipment well known to those skilled in the art of film forming.

[0079] Some of the advantageous / beneficial properties exhibited by the monolayer film produced according to the above method may include, for example, improved performance in: (1) tear strength in the cross direction (CD) of the film; (2) CD break stress in the CD of the film using the test method described in ASTM D882; (3) MD break stress in the machine direction (MD) of the film using the test method described in ASTM D882; and (4) static and dynamic COF between the sealant layer and the metal surface using the test method described in ASTM D1894. In addition, in general, the increase in the total acid % and neutralization % exhibited by the film leads to improved physical properties. In addition, the film can advantageously exhibit excellent sealing properties, such as improved hot tack, reduced heat seal initiation temperature, and improved gap filling.

[0080] When the film composition of the present invention is manufactured into a single-layer film, the manufactured film of the present invention exhibits the following tear strength characteristics in the CD of the film: in one general embodiment, ≥1 gf / mil (0.4 N / mm); in another embodiment, ≥5 gf / mil (1.9 N / mm); in yet another embodiment, ≥10 gf / mil (3.9 N / mm); and in yet another embodiment, ≥15 gf / mil (5.8 N / mm). In some embodiments, the films of the invention exhibit tear strength properties in CD as measured by the test method described in ASTM D1922: 1 gf / mil (0.4 N / mm) to 200 gf / mil (77 N / mm) in one general embodiment; 5 gf / mil (1.9 N / mm) to 150 gf / mil (58 N / mm) in another embodiment; 10 gf / mil (3.9 N / mm) to 100 gf / mil (39 N / mm) in yet another embodiment; and 10 gf / mil (3.9 N / mm) to 75 gf / mil (29 N / mm) in yet another embodiment. Below the general range, the abrasion resistance of the film will decrease; and above the general range, the abrasion resistance will increase.

[0081] The manufactured monolayer film also exhibits a CD stress at break in the CD of the film of ≤7,000 psi (48.3 MPa) in one general embodiment; ≤5,000 psi (34.5 MPa) in another embodiment; and ≤4,000 psi (27.6 MPa) in yet another embodiment. In some embodiments; the film exhibits a CD stress at break of 500 psi (3.4 MPa) to 7,000 psi (48.3 MPa) in one general embodiment; 500 psi (3.4 MPa) to 5,000 psi (34.5 MPa) in another embodiment; and 500 psi (3.4 MPa) to 4,000 psi (27.6 MPa) in yet another embodiment, as measured by the test method described in ASTM D882. Below the above general range, the film will not be able to withstand tension during downstream processes such as lamination or packaging conversion processes. Above the above general range, abrasion resistance is reduced.

[0082] And, the manufactured monolayer film exhibits a MD fracture stress on the MD of the film: in one general embodiment ≥1,000 psi (6.9 MPa), in another embodiment ≥2,000 psi (13.8 MPa), and in yet another embodiment ≥4,700 psi (32.4 MPa). In some embodiments, the film exhibits a MD fracture stress as measured by the test method described in ASTM D882: in one embodiment 1,000 psi (6.9 MPa) to 8,000 psi (55.2 MPa); in another embodiment 2,000 psi (13.8 MPa) to 7,000 psi (48.3 MPa); and in yet another embodiment 4,700 psi (32.4 MPa) to 6,000 psi (41.4 MPa). Below the above general range, the wear resistance of the film will decrease; and above the above general range, the wear resistance will increase.

[0083] In addition, the manufactured film exhibits static and dynamic COF between the sealant and the metal as follows: ≤1 in one general embodiment; ≤0.5 in another embodiment; and ≤0.35 in yet another embodiment. In some embodiments, the film exhibits static and dynamic COF between the sealant and the metal as measured by the test method described in ASTM D1894: 0.05 to 1.0 in one general embodiment; 0.10 to 0.5 in another embodiment; and 0.10 to 0.35 in yet another embodiment. Below the above general range, the film will be difficult to control and reduce packaging efficiency because the low COF will cause the film to slide uncontrollably when being pulled through the packaging machine. Above the above general range, packaging efficiency will also be reduced because the high COF will cause the film to stick to different points along the packaging line.

[0084] In addition to the above-described single-layer film structures, in some embodiments, the ARF may include two or more film layers combined together to form an ARF for food product packaging applications. For example, the ARF may be made of two, three, five, seven, nine or more layers. In one embodiment, the ARF includes a double-layer film structure comprising (1) an outer skin layer and (2) an inner ARF layer coextruded with the outer skin layer. For example, the double-layer film structure may be designated as an A / B film structure, wherein layer A is the outer skin layer and layer B is the inner ARF layer. The inner ARF layer B contacts the food product packaged in a packaging article such as a can or barrel. The outer skin layer A may be made of the same material as the inner ARF layer B; or the two layers A and B may be made of different materials.

[0085] In another embodiment, the ARF can be a three-layer film structure, including an outer skin layer, a tackifying adhesive layer, and an inner film lining layer. For example, the three-layer ARF can be designated as an A / B / C film structure, wherein the A layer is the outermost skin layer; the B layer is the adhesive layer; and the C layer is the innermost ARF layer. The adhesive layer B is disposed between the outer layer A and the ARF layer C. The outer layer A and the adhesive layer B can be made of the same material as the ARF layer C or a different material. The inner ARF layer C contacts the food product packaged in the package including the inner ARF layer C.

[0086] In other embodiments, the multilayer ARF of the present invention can be made from any number of layers greater than three using methods and equipment apparent to those skilled in the art of film manufacturing, provided that at least one layer of the multilayer film member is an ARF layer made from the film composition of the present invention. For example, the innermost layer (or film lining) of the package can be the ARF layer that contacts the food product packaged in the package. The ARF layer advantageously has an appropriate balance of properties such as wear resistance / scratch resistance, thinnability, and recyclability.

[0087] For the above-mentioned various multilayer film components, other layers (i.e., layers excluding the inner film lining layer of the present invention) can be formed by any material known in the art for multilayer films. Thus, for example, in one embodiment, the outer skin layer A of the above-mentioned double-layer structure can be formed by, for example, polyethylene (homopolymer or copolymer), and the polyethylene can be, for example, VLDPE, LDPE, LLDPE, MDPE, HDPE and mixtures thereof, as well as other polyethylenes known in the art. For example, in another embodiment, the outer skin layer A can be formed by polyethylene (homopolymer or copolymer), a non-polyethylene polymer (e.g., polypropylene) or a blend of polyethylene and a non-polyethylene polymer.

[0088] Examples of some commercially available materials that can be used for the outer skin layer A of the film of the present invention may include, for example, DOWLEX TM 2045G、DOWLEXTM NG 5045P、DOWLEX TM 2645G, DOWEX TM 2049G、DOWLEX TM 2038.68G, DMDA-6200NT 7, DMDA-6400NT 7, DOWLEX GM 8070G, LDPE 611A, AGILITY TM 2000、AGILITY TM 1023, LDPE TM 150E and LDPE TM 310E (both available from Dow Chemical Company); Enable TM 2703 and Enable TM 3505 (both available from ExxonMobil); Lutene TM BE0400 (available from LG Chem); and mixtures thereof.

[0089] The above-mentioned various resin polymer materials can have various density and melt index characteristics. For example, in a preferred embodiment, the outer skin layer A can be made of LDPE resin, wherein the resin has: a density of 0.915 g / cc to 0.928 g / cc in a general embodiment; and a melt index I2 of 0.10 g / 10 min to 30 g / 10 min in a general embodiment.

[0090] When used in the multilayer films of the present invention, the thickness of the outer skin layer A can be, for example: 2 μm to 380 μm in one general embodiment; 7 μm to 260 μm in another embodiment; and 7 μm to 100 μm in yet another embodiment.

[0091] In a multilayer film structure, one or more layers B as adhesion-promoting tie layers may include, for example, a methylene-acrylic acid copolymer, such as that available from the Dow Chemical Company under the trade name NUCREL TM A series of copolymers; ethylene-vinyl acetate copolymers and mixtures thereof.

[0092] When used in the multilayer film of the present invention, the thickness of the tie layer B can be, for example: 2 μm to 380 μm in one general embodiment; 7 μm to 260 μm in another embodiment; and 7 μm to 100 μm in yet another embodiment.

[0093] The film composition used to make the ARF layer C of the present invention is described above with reference to a single-layer film structure, that is, the ARF layer C can be made from a film resin formulation or composition comprising a combination, blend or mixture of the following components: (a) at least one ionomer of the acid copolymer; (b) at least one anti-slip additive, such as CONPOL TM 20S1; (c) at least one anti-blocking additive such as CONPOL TM 13B; (d) at least one chill roll release additive such as CONPOL TM 5R; and (e) optionally, if desired, one or more additives different from components (a) to (d).

[0094] Once the ARF layer is fabricated, it may be attached to the other layers by coextrusion or lamination as is well known to those skilled in the art of film fabrication.

[0095] When used in the multilayer films of the present invention, the thickness of the ARF layer is, for example: 2 μm to 380 μm in one general embodiment; 7 μm to 260 μm in another embodiment; and 7 μm to 100 μm in yet another embodiment.

[0096] The density of the ARF layer is typically from 0.900 g / cc to 0.980 g / cc in one embodiment, from 0.920 g / cc to 0.980 g / cc in another embodiment, and from 0.935 g / cc to 0.980 g / cc in yet another embodiment.

[0097] The melt index of the ARF layer is typically from 0.5 to 50 g / 10 min in one embodiment, from 1 to 30 g / 10 min in another embodiment, and from 2 to 15 g / 10 min in yet another embodiment.

[0098] In a broad embodiment of the present invention, a method for making a multilayer film includes, for example, using any conventional film forming method, such as cast film method, blown film method, extrusion coating method and other methods and equipment well known to those skilled in the art of film forming.

[0099] As described above, some of the advantageous properties exhibited by the ARF products manufactured from the film composition using the above-mentioned method of the present invention may include, for example: (1) the ARF exhibits an advantageously high level of abrasion and scratch resistance in the presence of oils and seasonings; (2) the manufactured container packaging products including the ARF of the present invention can be thinned by up to 80% without adversely affecting the shelf life of food products in contact with the ARF; and (3) the manufactured container packaging products including the ARF of the present invention can be manufactured so that the manufactured container packaging products can be recyclable.

[0100] In some embodiments, the container packaging product comprising the manufacture of the ARF of the present invention can be thinned: up to 80% in one embodiment, up to 70% in another embodiment, up to 60% in another embodiment, and up to 50% in another embodiment. In other embodiments, the container packaging product comprising the manufacture of the ARF of the present invention can be thinned: 0% (no thinning) to 80% in a general embodiment, 5% to 70% in another embodiment, 5% to 60% in another embodiment, and 5% to 50% in another embodiment. In some embodiments, the container packaging product comprising the manufacture of the ARF of the present invention can be thinned: 10% to 80% in one embodiment, 10% to 70% in another embodiment, 10% to 60% in another embodiment, and 10% to 50% in another embodiment. In other embodiments, the container packaging product comprising the manufacture of the ARF of the present invention can be thinned: 20% to 80% in one embodiment, 20% to 70% in another embodiment, 20% to 60% in another embodiment, and 20% to 50% in another embodiment.

[0101] Without being limited to the following theory, it is theorized that by balancing: (1) neutralization of the ionomer and increase in free acid; (2) appropriate ion selection for neutralization and (3) reduction in the COF of the film, a properly manufactured container packaging product comprising the ARF of the present invention can be manufactured to have the appropriate beneficial properties that are required for the film to be suitable for packaging applications.

[0102] When the total film product has several layers and at least one layer is the ARF layer of the present invention, the overall ARF has several advantageous properties. For example, the entire film made of multiple layers exhibits improved properties such as wear resistance, scratch resistance, and oil resistance. And based on the COF of the resulting film product, the film can provide high sealant performance and excellent machinability.

[0103] The ARF of the present invention prepared as described above can be used, for example, in food product packaging applications. For example, a packaging container for packaging food products (e.g., a bottle, a bag, a pouch, a purse bag such as a pillow bag, or a can such as a composite can) can include a multilayer structure comprising a combination of several layers of different materials, such as paper, a gas and / or moisture barrier material, and a polymer resin layer, wherein at least one of the layers including the resin layer is an ARF layer of the present invention.

[0104] As previously mentioned, containers such as rigid containers for food packaging may have a multilayer film structure, with the innermost film layer (i.e., "film lining") of the container being an ARF layer. The ARF layer is typically in direct contact with the food product and needs to have high wear and scratch resistance properties sufficient to maintain the appropriate shelf life of the packaged food product. This is especially true when the food product contains sharp edges that wear and scratch the interior of the rigid container during handling and transportation. By way of illustration, but not limitation, food products that can be packaged in a rigid container having an ARF layer as the film lining of the present invention include, for example, food products that have rough and sharp edges that can cause the film lining to be worn and scratched, such as nuts, cereals, mixed nuts, pretzels, and the like.

[0105] refer to Figure 1 , a multilayer structure including an ARF layer of the present invention is shown. For example, the multilayer structure may be a rigid container package generally indicated by reference numeral 10. Typically, the rigid container package 10 is made of several layers of mixed materials, i.e., made of various different substrates, such as paper, plastic, metal, etc.

[0106] Reference again Figure 1 , shows a multi-substrate structure 10 of the present invention, which is made of various substrates, including, for example, a paper layer 11, a LDPE polymer or other polymer resin layer 12, and an ARF layer 13. The resulting multi-substrate structure 10 (such as a rigid container with an ARF layer of the present invention) is made of paper and plastic, so that the rigid container 10 is advantageously recyclable. In some embodiments, other substrates (not shown), such as gas and / or moisture barriers or different plastic substrates, can be used as one of the layers of the rigid container (multi-layer structure 10). In some embodiments of the present invention, the ARF layer 13 of the present invention exhibits improved wear, scratch, oil and seasoning resistance when used as a film liner in a rigid container 10, for example, a rough food product is packaged in the rigid container. In the above examples, the film liner of the rigid container exhibits improved wear, scratch, oil and seasoning resistance, while maintaining the desired shelf life of the food product even when the ARF layer 13 of the present invention is thinned to form a thinner layer.

[0107] Example

[0108] The following Inv.Ex. and Comp.Ex. (collectively referred to as "Examples") are given herein to further illustrate the features of the present invention, but are not intended to be construed as limiting the scope of the claims, either explicitly or by implication. The Inv.Ex. of the present invention are represented by Arabic numerals, and the Comp.Ex. are represented by letters of the alphabet. The following experiments analyze the performance of the embodiments of the compositions described herein. Unless otherwise indicated, all parts and percentages stated are by weight based on total weight.

[0109] Abbreviations and nomenclature

[0110] Various terms, abbreviations, nomenclatures and raw materials used in the examples (Inv.Ex.) of the present invention and comparative examples (Comp.Ex.) are explained as follows:

[0111] "EMAA" means ethylene methacrylic acid.

[0112] "EAA" means ethylene acrylic acid.

[0113] "SBR" is the suffix used herein to indicate that "anti-slip (S)", "anti-block (B)" and "chill roll release (R)" additives are added to the formulation.

[0114] "iBA" means isobutyl acrylate.

[0115] raw materials

[0116] The ingredients / raw materials used in the examples are explained below:

[0117] SURLYN TM is a series of ionomer polymer resin products available from The Dow Chemical Company.

[0118] CONPOL TM is a series of additives used in the above polymer resin products. The additives may include, for example, anti-slip additives, anti-block additives, and chill roll release additives; and the additives are available from The Dow Chemical Company.

[0119] Resin preparation for ARF

[0120] General procedure for preparing ARF preparations

[0121] Samples of the ARF resin formulations (film compositions) described in Table I were prepared by dry blending various polymer pellets of components (a), (b), (c), (d), and optionally (e) using a dry blender such as a tumble mixer or a ribbon blender.

[0122]

[0123] membrane

[0124] General procedure for preparing ARF

[0125] After preparing samples of the resin formulations (film compositions) described in Table I, various ARF samples described in Table II were made using the formulations described in Table I. The film compositions were made into ARF specimens according to the following general procedure:

[0126] The ARF samples used in the examples are cast films, and the ARF is manufactured using a cast film process. Each ARF sample is a single-layer film structure. Each sample film has a total thickness of 50.8 μm.

[0127] The film samples were cast using a laboratory scale cast film line manufactured by COLLIN and equipped with a single 30 mm extruder. The film manufacturing parameters / conditions were as follows:

[0128] (1) Specification = 2mil (50.8μm)

[0129] (2) Die gap = 20mil (0.508mm)

[0130] (3) Die size = 10 inches (250 mm)

[0131] (4) Air gap = 0.75 inches (19.05 mm)

[0132] (4) Screw speed = 42 rpm

[0133] (5) Melt pressure = 35 MPa

[0134] (6) Output = 5kg / hr

[0135] (7) Linear speed = 0.112 m / s

[0136] (8) Stretch ratio = 10:1

[0137] (9) Cooling roller temperature = 18°C

[0138] (10) Film width after online cutting = 9 inches (228.6 mm)

[0139] (11) Melt temperature = 203°C

[0140] (12) The extruder temperature curves in different areas are as follows:

[0141]

[0142] Test Method

[0143] Average breaking stress in transverse and longitudinal directions

[0144] Typically, the average stress at break test is performed according to the procedure described in ASTM D882. When the film is stretched at a strain rate of 20 inches / minute (8.47 mm / s) under uniaxial tension, the tensile force versus displacement curve is measured, wherein the longitudinal or transverse direction of the film is parallel to the displacement direction. The stress versus strain curve is calculated from the measured force versus displacement curve, and the stress at break is taken as the stress at the failure (fracture) point of the film. More specifically, according to the procedure described in ASTM D882, the tensile properties of thin plastic sheets are determined using the following method.

[0145] The properties of the film were measured using the tensile test when tested under uniaxial extension. After film production, the film to be tested was conditioned at 23°C (+ / -2°C) and 50% RH (+ / -10%) for at least 40 hours according to ASTM standards. The standard test conditions were 23°C (+ / -2°C) and 50% RH (+ / -10%) according to the procedure described in ASTM D882.

[0146] Tensile test strips are cut from the sheet in the longitudinal direction (MD) and cross direction (CD), if applicable. The cut strips are 1 inch (25.4 mm) wide and approximately 8 inches (203.2 mm) long. For standard tensile testing, the test strip samples are loaded onto the tensile test frame using the clamp jaws (flat rubber on one side of the jaws and clamps on the other side) with the gauge length (clamp to clamp distance) set to 2 inches (50.8 mm). The test sample is then strained at a crosshead speed of 20 inches / minute (8.47 mm / s). From the resulting load-displacement curve, the yield strength and yield strain, tensile strength and tensile strength at break, fracture strain, and fracture energy can be determined. Strain is calculated using the crosshead extension divided by the original gauge length (2 inches) (50.8 mm). Stress is reported as engineering stress or nominal stress and is the load divided by the original cross-sectional area.

[0147] Average normalized Elmendorf tear strength in the transverse direction

[0148] The force in grams required to propagate a tear across a film sample was measured using a modified Pro-Tear electronic Elmendorf tear tester. Acting through gravity, the pendulum swings in an arc, tearing the sample from the pre-cut slit. The tear propagates in the cross-machine direction.

[0149] Elmendorf Tear Test The Elmendorf-type tear tester is used to determine the average force required to propagate a tear through a specified length of plastic film or nonrigid sheet material after the tear is initiated.

[0150] After film production, the films were conditioned at 23°C (+ / -2°C) and 50% RH (+ / -10%) for at least 40 hours according to ASTM standards. According to ASTM standards, standard testing conditions are 23°C (+ / -2°C) and 50% RH (+ / -10%).

[0151] The force required to propagate tearing across a film or sheet sample was measured in grams using a precisely calibrated pendulum device. Acting by gravity, the pendulum swings in an arc, thereby tearing the sample from the pre-cut slit. One side of the sample is fixed by the pendulum and the other side is fixed by a fixed member. The energy loss of the pendulum is indicated by a pointer or an electronic scale. The scale indication is a function of the force required to tear the sample. The sample used is a "constant radius geometry" as specified in D1922. Samples cut from the MD and CD directions are usually tested. Before testing, the sample thickness is measured at the center of the sample. A total of 15 samples were tested for each direction (MD and CD), and the average tear strength was reported. Samples torn at an angle of> 60° to the vertical are described as "oblique" tearing-it should be noted that this tearing, although the strength value is included in the average strength calculation.

[0152] Static (dynamic) friction coefficient (sealant to metal)

[0153] In general, the static and dynamic coefficient of friction tests are based on the procedure described in ASTM D1894. Data is generated using a stretch frame with a COF attachment. The plastic film is secured to a flat surface and placed in contact with a flat, weighted metal surface. The metal sheet is moved at a constant speed over the surface of the plastic film, and the force required to move the metal sheet is used to calculate the static and dynamic coefficients of friction. The data reported are the average static and dynamic energies. Testing is performed only at 23°C. More specifically, the following method is used to determine the static and dynamic coefficients of friction of plastic films and sheets according to the procedure described in ASTM 1894.

[0154] The test described in ASTM D1894 is used to measure the static and dynamic coefficients of friction of plastic films / sheets. The coefficient of friction (COF) can be tested for different surface pairings: film-to-film (inside-inside, outside-outside, or inside-outside) or film-to-metal (inside-metal or outside-metal).

[0155] The film samples to be tested are conditioned at 23°C (+ / -2°C) and 50% RH (+ / -10%) for at least 40 hours according to ASTM standards. According to ASTM standards, standard test conditions are 23°C (+ / -2°C) and 50% RH (+ / -10%).

[0156] The test was performed using an INSTRON 5564Universal testing machine. Samples of the film samples were cut into 3 inches by 6 inches (76.2 mm by 152.4 mm). A B-type slide was used, which was a square of 2.5 inches by 2.5 inches (63.5 mm by 63.5 mm) and weighed 195 g. The sample was tightly wrapped around the slide, aligning the longitudinal direction (MD) parallel to the direction of movement. This was aided by the use of double-sided tape pre-attached to the top surface of the slide. Make sure there are no wrinkles on the surface of the film to be tested. A COF measuring fixture consisting of a rigid plate with a low-friction pulley is connected to the fixed base of the device. A metal plate is then placed on top of the above-mentioned rigid plate and subsequently used as a plane on which the slide is driven. The crosshead is then driven at a speed of 6 inches / minute (2.54 mm / s) to travel a distance of 3 inches (76.2 mm). The force when the sample starts to move (the initial peak in the load-displacement data) is the static force (F S The average load calculated between 1 / 2 inch (12.7 mm) and 3 inches (76.2 mm) of movement is the dynamic force (F K ). Static COF(μ S ) is the static force (F S ) to the normal force (= weight of the skateboard, W). Similarly, the dynamic COF (μ K ) is the dynamic force (F K ) to the normal force. Five samples from the same film roll (sample) were tested. Each sample was tested once. After testing each of the five samples, the average of the test results was reported.

[0157] Total acid level

[0158] The total acid level is the initial weight percent of ethylene acid functionality incorporated into the copolymer.

[0159] % neutralized acid

[0160] The ionomer is produced by adding a salt to an ethylene acid copolymer during the compounding process. The neutralization percentage of the ionomer is determined by the ratio of the mole percent of salt added to the mole percent of acid functional groups of the ethylene acid copolymer. The weight percent of neutralized acid of the ionomer is determined by the product of the neutralization percentage and the initial weight percent of acid functional groups of the ethylene acid copolymer.

[0161] Free acid level

[0162] The weight percent free acid is obtained by the difference between the initial weight percent acid functionality of the ethylene acid copolymer and the weight percent neutralized acid.

[0163] Average abrasion resistance rating in the presence of oils and seasonings

[0164] In order to grade the wear resistance of ARF, the monolayer film samples of ARF were subjected to abrasion procedures using a vibrating table process. The monolayer film samples with a thickness of 2mil (0.0508mm) were produced using the cast film process. In order to determine the average wear resistance grade of each monolayer film sample, each monolayer film sample was first cut into 210mm × 297mm sheets, wherein the MD direction of the cast film was parallel to the long side of 297mm. Three film samples were cut from each sample film roll. A 5.5oz (155.9g) covered cylindrical can was used, and a coarse food product was housed in the can, which also included seasonings and oils on the surface of the food product. The coarse food contents in the cylindrical can were emptied and cleaned. Each sheet sample was rolled into a cylinder and inserted into an empty, clean cylindrical can so that the film was lined in the inside of the can. The coarse, seasoned oily food product was then carefully reinserted into the can to prevent the food product from being damaged. The cylindrical can lid was fixed back on the top of the cylindrical can. The cylindrical jar containing the rough food product was placed on a shaker table and vibrated vertically at 5 Hz frequency and 0.7 inch (17.78 mm) displacement for 24 hours at ambient temperature. After the shaker table process, the membrane was removed from the cylindrical jar, cleaned, and photographed.

[0165] Images of each single layer film sample were taken before and after the film sample was treated by the above-described abrasion procedure. The components used to obtain images of the film samples (imaging the film to show the worn and scratched areas of the film) included an optical camera and a circular polarizing lens, combined with a white backlight for the film and a linear polarizing film to enhance the contrast of the worn and scratched areas of the film; and reduce glare.

[0166] refer to Figure 2 , shows a black and white image of a single (monolayer) membrane sheet of the prior art, generally indicated by reference numeral 20. The membrane sheet 20 is made using a known ionomer, such as a copolymer of ethylene and methacrylic acid, such as SURLYN available from The Dow Chemical Company. TM . Figure 2 The image of the membrane sheet 20 is the membrane sheet before the membrane sheet is subjected to the wear process. Figure 2 In FIG. 1 , three regions (zones or sections) of a membrane sheet 20 are shown, generally indicated by dashed circles 21 , 22 and 23 of the membrane sheet 20. Figure 2 In the embodiment, the membrane sheet 20 does not contain any wear in the regions 21, 22 and 23. Figure 3 As shown, after the film sheet 20 undergoes a wear process, a worn film sheet is formed, and various wear and scratches exist on the surface of the film sheet.

[0167] refer to Figure 3 , showing a prior art single (single layer) membrane sheet (generally indicated by reference numeral 30) on a membrane sheet (from Figure 2 ) after the wear process. Figure 3 , shows a worn film sheet 30 having several wear and / or scratches generally located in the wear and scratch areas generally indicated by dashed circles 31 , 32 and 33 of the film sheet 30 . Figure 3 Wear and / or scratches on the membrane sheet 30 shown in FIG. 5 may be indicated by black or white areas, such as those areas indicated by reference numerals 34 , 35 , and 36 located in areas 31 , 32 , and 33 , respectively.

[0168] refer to Figure 4 , shows a black and white image of a single (single layer) membrane sheet of the present invention, generally indicated by reference numeral 40, made using a composition including the ionomer of the present invention. Figure 4 The image of the membrane sheet 40 is the membrane sheet before the membrane sheet is subjected to the wear process. Figure 4 In FIG. 4 , three regions are shown generally indicated by dashed circles 41, 42 and 43 of the membrane sheet 40. Figure 4 In the embodiment, the membrane sheet 40 does not contain any wear in the areas 41 and 42 of the membrane sheet 40. Figure 6 As shown, after the film sheet 40 undergoes a wear process, a worn film sheet is formed, and various wear and scratches exist on the surface of the film sheet.

[0169] refer to Figure 5 , showing a single (single layer) film sheet of the present invention (generally indicated by reference numeral 50) on a film sheet (from Figure 4 ) after the wear process. Figure 5 , showing a worn membrane sheet 50 having wear and / or scratches. Figure 5 The wear and / or scratches in the membrane sheet 50 are generally located in the wear and scratch areas generally indicated by the dashed circles 51 , 52 and 53 of the membrane sheet 50. Figure 5 Wear and / or scratches on the film sheet 50 shown in FIG. 5 may be indicated by black or white areas, such as those indicated by reference numerals 54, 55, and 56 located in areas 51, 52, and 53, respectively. Figure 3 Compared with the worn membrane sheet 30, Figure 5 The worn membrane sheet 50 is shown to have less wear and / or scratches.

[0170] Prepare Figure 2-Figure 5 The images shown in were used to determine the amount of wear / scratching that occurred on the surface of the inventive film sheet 5 compared to the conventional film after the film was subjected to the abrasion process. The worn and scratched areas of the film sheets were also used for the purpose of rating the abrasion resistance of the film.

[0171] Abrasion resistance rating method

[0172] The rating system for determining the abrasion resistance rating Y for each film was used to semi-quantitatively compare the films to each other based on the appearance of the worn and scratched areas on each film. The following system using equation (II) was used for the abrasion resistance rating Y, where:

[0173] Y = m1×A1+m2×A2+m3×A3+m4×A4+m5×A5 equation (II);

[0174] In equation (II), m n is a multiplication factor describing the severity of wear for n=1, 2, 3, 4 or 5; and A n is corresponding to the severity m n Table II and Table III describe the factors A used in the above rating system and equation (II), respectively. n and m n To help determine m n and A n A grid of 1 cm x 1 cm squares was overlaid on each film image and the squares that overlapped any worn areas were outlined to indicate the presence of wear. Based on the severity of the wear, the area within each outlined square was assigned a value m. n The guidelines for this evaluation are specified in Table III. n The total area of ​​the outline squares is added and divided by the total area of ​​the image to determine A according to Table II n The value of .

[0175] Table II - Wear Areas

[0176]

[0177] Table III - Factor "m"

[0178]

[0179] Test Results

[0180] The results of the properties of each film composition tested are described in Table IV.

[0181] Table IV - Properties of Film Compositions

[0182]

[0183] Notes to Table IV: *"NC" stands for "Not Calculated" because the composition is a blend of terpolymer resin and IONOMER3.

[0184] **"NC" stands for "Not Calculated" because the base resin is a terpolymer resin containing 10% total acid and 10% iBA.

[0185] ***"NC" stands for "Not Calculated" because this composition is a blend of terpolymer resin and IONOMER 8.

[0186] (1) "iBA" stands for "isobutyl acrylate." The composition is not an ionomer.

[0187] The results of the characteristics and performance of each ARF tested are described in Table V.

[0188] Table V - Film Characteristics and Performance

[0189]

[0190] Notes to Table V: (1) "SBR" indicates that anti-slip, anti-block and chill roll release additives have been added.

[0191] (2) Terpolymer resins are not ionomers.

[0192] (3) "NA" stands for "Not Applicable" because the terpolymer is not an ionomer.

[0193] Discussion of Results

[0194] As shown in Table II, the ARF of Example 2 of the present invention has good characteristics and good performance. For example, the wear resistance grade (Y) is one of the beneficial performance indicators. The higher Y, the better the performance. As described in Table II, Y of Example 2 of the present invention is the highest, indicating that Example 2 of the present invention has the highest wear resistance in the presence of oil / grease and seasoning compared to other comparative examples. Based on equation (I), other physical properties of the film are related to Y. The relationship defined by the linear equation shows the importance of each physical property value to the wear resistance grade.

[0195] The wear resistance rating is an important performance indicator of the film; and the higher the wear resistance rating, the better the wear resistance of the film. The wear resistance rating of the ARF of Example 2 of the present invention is the highest, indicating that Example 2 of the present invention has the highest wear resistance in the presence of oil / grease and seasoning compared to the comparative example. Based on equation (1), other physical properties of the ARF are related to the wear resistance rating. The relationship defined by the linear equation, equation (1), shows the importance of each physical property value to the wear resistance rating.

Claims

1. A composition for making a wear-resistant film, the composition comprising: (a) at least one ionomer of ethylene (meth)acrylic acid copolymer; (b) at least one anti-slip additive; (c) at least one antiblock additive; (d) at least one chill roll release additive; and (e) optionally, one or more additives different from components (a) to (d); wherein the at least one ionomer of the ethylene (meth)acrylic acid copolymer, component (a), is at least one sodium-based ionomer of an ethylene acid copolymer having (i) a neutralized acid content greater than 7 wt %, (ii) a free acid content greater than 9 wt %, and (iii) a total acid content greater than 16 wt %.

2. The composition of claim 1, wherein the at least one anti-slip additive, component (b), is added to the composition as a masterbatch comprising the anti-slip additive and an ethylene-(meth)acrylic acid carrier resin; wherein the at least one anti-block additive, component (c), is added to the composition as a masterbatch comprising the anti-block additive and an ethylene-(meth)acrylic acid carrier resin; and wherein the at least one chill roll release additive, component (d), is added to the composition as a masterbatch comprising the chill roll release additive and an ethylene-(meth)acrylic acid carrier resin.

3. The composition of claim 1, wherein the at least one anti-slip additive, component (b), is an oleyl palmitamide additive; wherein the at least one anti-block additive, component (c), is a silica additive; and wherein the at least one chill roll release additive, component (d), is a behenamide additive.

4. The composition according to claim 1, wherein the composition is made into a film member having a wear resistance grade value Y greater than 6.0 according to the following equation (I): wherein Y is an abrasion resistance rating greater than 6.0; wherein A is an average tensile stress at break in the transverse direction of the membrane member; Wherein B is the average tensile breaking stress in the longitudinal direction of the membrane member; and Wherein C is the average normalized Elmendorf tear in the transverse direction of the film member.

5. The composition of claim 1, wherein the concentration of the at least one ionomer of the acid copolymer, component (a), of the composition is from 20 wt % to 100 wt %; wherein the concentration of the at least one anti-slip additive, component (b), of the composition is greater than 0.05 wt %; wherein the concentration of the at least one anti-block additive, component (b), of the composition is greater than 0.05 wt %; and wherein the concentration of the at least one chill roll release additive, component (d), of the composition is greater than 0.05 wt %.

6. The composition of claim 1, wherein the composition, when formed into a film, provides a film that exhibits one or more of the following properties: a tear strength greater than or equal to 0.4 N / mm in CD; a CD stress at break less than or equal to 48.3 MPa in CD and a MD stress at break greater than or equal to 6.9 MPa in MD using the test method described in ASTM D882; and a static and kinetic coefficient of friction less than or equal to 0.35 between sealant and metal using the test method described in ASTM D1894.

7. A method for producing a composition for making a film, the method comprising mixing: (a) at least one ionomer of an acid copolymer; (b) at least one anti-slip additive; (c) at least one anti-block additive; (d) at least one chill roll release additive; and (e) optionally, one or more additives different from components (a)-(d).

8. A wear-resistant film comprising at least one single-layer film or at least one multi-layer film, wherein the at least one single-layer film or the at least one multi-layer film comprises at least one layer, the at least one layer comprising a film made from the film composition according to claim 1.

9. The film of claim 8, wherein the film exhibits at least one or more of the following properties: a tear strength greater than or equal to 0.4 N / mm in CD; a CD stress at break less than or equal to 48.3 MPa in CD and a CD stress at break greater than or equal to 6.9 MPa in MD using the test method described in ASTM D882; and a static and kinetic coefficient of friction less than or equal to 0.35 between sealant and metal using the test method described in ASTM D1894.

10. A method for producing the film according to claim 8, the method comprising the steps of: (I) mixing (a) at least one ionomer of an acid copolymer; and (b) at least one anti-slip additive; (c) at least one antiblock additive; (d) at least one chill roll release additive; and (e) optionally, one or more additives different from components (a) to (d); and (II) forming at least one monolayer film or at least one multilayer film from the film mixture of step (I); wherein the at least one monolayer film or the at least one multilayer film comprises at least one layer, and the at least one layer comprises a film made from the film composition of step (I).

11. An article or package comprising an article or package produced from the film according to claim 8.

12. The article or package of claim 11, wherein the article or package is a food product packaging container comprising a multilayer structure, wherein the multilayer structure comprises at least one layer comprising a film made from the film composition of claim 1; and wherein the film has: (i) sufficient wear and scratch resistance; and (ii) sufficient oil and seasoning resistance to avoid environmental stress cracking, so that the film liner can contact rough, seasoned and oily food products without adversely affecting the wear and scratch resistance of the film liner.